Influence of Critical Soft Factors on Quality Improvement and Organizational Performance - Abdullah, Muhammad Madi (2007)
This study was to determine the relationships of selected variables, namely management commitment, customer focus, employee involvement, training and education, reward and recognition and supplier relationship in predicting quality improvement (QI) and their relationships to organizational performance (OP). The survey research provided a method of empirical verification utilizing stratified and simple random sampling to determine the relationships between variables at the time of study. The sample consisted of 255 firms from the electrical and electronics sector. The selection of respondents involves a complete list of electrical and electronics firms within West Malaysia which was obtained from directory list Federation of Malaysian Manufacturers- Malaysian External Trade Development Corporation (FMM-MATRADE). The quantitative data were subjected to various descriptive-correlation statistical analyses, multiple regression, mediation analyses, and structural equation modeling. In this study, the findings support the relationship between the independent variables and QI. Five variables, namely management commitment, customer focus, employee involvement, training and education, and reward and recognition explained 93.8% (F = 748.342, p = 0.0001) of QI. Only four variables, namely management commitment, customer focus, employee involvement, and reward and recognition significant predictors of organizational performance, and collectively these variables explained 25.6% (F = 15.636, p = 0.0001) of the variation in OP. QI is a significant predictor in determining OP. The effect of the QI as a mediator between all the exogenous variables and OP is found. Reward and recognition exerts the strongest total effect (0.688) on OP whereas customer focus emerged as having the second strongest total effect (0.588) on OP. The implications as well as the limitations of the study were discussed in detail. Future research suggestions were advocated, in particular, the replication of this study to other industry. Further work is also needed to develop a new model and identify the relationship between the critical soft and hard factors and their joint contribution to QI and OP. The implications as well as the limitations of the study were discussed.